Locative adverbs in the subject position in Brazilian Portuguese (Revista de Estudos da Linguagem, 2024)
This article examines the syntactic and semantic properties of locative adverbs in Brazilian Portuguese to verify whether they occupy the subject position. We observe that adverbs can occupy the subject position as well as locative NPs. We propose that, contrary to full DPs, adverbs do not bear the number feature inherently, manifesting only the person feature. Following Baker (2003), we propose that locative adverbs bear a referential index. The conclusion is that locative adverbs in subject position are generated as VP adverbs or locative arguments, bearing the following formal features: [+deictic] and [+ (3rd) person].